Effects of different carbon sources on the oxidative stress tolerance of Aspergillus niger HY2 isolated from spoiled paddies. Issue 1 (8th September 2022) - Tan, Song; Xu, Yuancheng; Wu, Hongying; Niu, Ajuan; Yin, Xiaoyu; Wang, Guangyu; Qiu, Weifen
Abstract: Fungi often experience oxidative stress in response to the environment during growth. In this study, Aspergillus niger HY2, whose presence easily results in paddy mildew, was used to investigate the effects of different carbon sources on morphological development, reactive oxygen species (ROS) metabolites, and antioxidant enzymes activities. Morphological development mainly includes the changes in conidial production and colony diameter. ROS metabolites production include the content of hydrogen peroxide (H2 O2 ), superoxide anion (O2 · − ), and malondialdehyde (MDA). The results indicated that A. niger HY2 adapted to H2 O2 exposure by decreasing growth and increasing the activities of some antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Different carbon sources also affected the expression of the developmental-specific gene flbA and the oxidative stress tolerance-related gene cat . When incubated with glucose, sucrose, and xylose as carbon sources, A. niger exhibited stronger oxidative stress tolerance, but when incubated with maltose as a carbon source, A. niger exhibited relatively poor oxidative stress tolerance. Our results can provide a theoretical basis for further understanding mechanisms of metabolic adaptation and developing targeted strategies to control the spoilage caused by A. niger . Abstract : Aspergillus niger HY2 was used to investigate the effects of different carbon sources on morphological development, reactive oxygen species metabolites, and oxidative stress tolerance.